Finding the Correlation between Formative and Summative Assessments by Spearman’s Correlation Coefficient: A Case Study - Sokkalingam, Rajalingam; Oo, Z. (Cutin University Sarawak, Malaysia, 2011)
Academic progresses of students are measured by using variety of statistical analysis techniques like central tendency, variability, percentiles and others. These measures help the teaching professionals to understand their student progress in their class. A relatively simple technique that can be used for exploratory data analysis is the Spearman rank correlation coefficient. In this paper the authors describe how the Spearman rank correlation coefficient can be used as a statistical tool to find out the correlation between two different types of assessments for a mathematics unit as a case study. This method is perhaps the simplest method for calculation of coefficient correlation. Is a non parametric technique for evaluating the degree of linear association or correlation between two independent variables. It is operates on the ranks of the data rather than the raw data. The case study result show that existence of a positive correlation of medium order between the formative and summative assessments. That is, increase in formative assessment the summative assessment also increase. In other words, some students who scored high in the formative assessment only managed to get medium scores in the summative assessment and vice versa.